EVAKUASI KORBAN BANJIR DI MONCONGLOE LAPPARA KECAMATAN MONCONGLOE KABUPATEN MAROS - Sharon, St Salmah; Arif, Muh; Tanesia, Cindy Yoel; Suade, Yuyun Karystin Meilisa; Erwin, Erwin (FKIP Universitas Wisnuwardhana, 2023)
This community service partner is the Bukit Baruga II Maros Complex Community which was affected by the flood. The purpose of this service is to evacuate flood victims in MoncongLoe Lappara, Moncongloe District, Maros Regency by preparing temporary shelters for flood victims. The form of this service activity is the preparation and implementation directly to the point/location affected by the flood by evacuating the flood victims. Visiting people's homes by giving directions to immediately go to the shelter that has been prepared. This is done to avoid the occurrence of flood victims. The flood handling method is to coordinate with the local government, namely the Bukit Baruga complex's family gathering, making evacuation routes to evacuation sites. The results of the service showed that all the people of Moncongloe Lappara, Moncongloe District, Maros Regency could be evacuated to a safer place/temporary shelter in the courtyard area of the mosque in the complex and there were no fatalities in the event of a flood. Residents, especially the elderly and children, are in a safe place until the flood conditions start to recede and they can return to their homes. The evacuation was carried out together with the Bukit Baruga complex family gathering together with the government of Moncongloe Lappara village. With the collaboration of all parties, the government, community members and academics residents can save themselves from flood disasters.